Inflammation centered muscle signature of sarcopenia from postmenopausal women in Shanghai China - Fan, Yongqian; Lin, Shangjin; Ling, Ming; Cui, Tao; Chen, Cong; Yang, Fengjian (Frontiers in Cell and Developmental Biology, 2025)
IntroductionSarcopenia reflects age-related failure of muscle maintenance and regeneration, with chronic low-grade inflammation disrupting the satellite cell niche. Validated tissue biomarkers that connect inflammaging to clinical phenotypes remain limited. We sought to define an inflammation-centered muscle transcriptomic signature in postmenopausal women from Shanghai China and to assess its association with case–control status and muscle phenotypes.MethodsWe prospectively enrolled 20 women undergoing femoral fracture surgery including sarcopenia (n = 8) and controls (n = 12). Vastus lateralis biopsies underwent RNA sequencing. Differentially expressed genes were identified and intersected with inflammation-associated genes from GeneCards. Random-forest models prioritized a minimal marker set. Discrimination was assessed with receiver operating characteristic analysis. Associations with appendicular lean mass, handgrip strength and calf circumference were tested.ResultsWe detected 301 differentially expressed genes enriched for p53, MAPK, TNF and NF-κB signaling together with ubiquitin-mediated proteolysis and cellular senescence. Intersection with the inflammation catalogue yielded 22 candidates that separated cases from controls by unsupervised clustering. Random-forest ranking nominated a five-gene panel JUN, SOCS3, CP, PTEN and C4B that showed strong single-gene discrimination with areas under the curve from 0.830 to 0.906. Higher expression of these genes was inversely associated with muscle quantity and strength.DiscussionThis work is a pilot study that delineates an inflammation-associated transcriptomic phenotype of sarcopenia in postmenopausal women. These markers nominate testable inflammatory pathways and provide a rationale for validation studies designed to determine whether non-invasive surrogates or larger cohorts can substantiate their translational relevance.